KEMAMPUAN PERTUMBUHAN EKONOMI DAN INVESTASI DALAM MENJELASKAN PENGANGGURAN DI KALIMANTAN BARAT PERIODE 2010-2014 - B01110061, ADRIANUS TEGUH J TEGUH J (Jurnal Pembangunan dan Pemerataan, 2016)
This thesis entitled "The Ability of Economic Growth And Investment InExplaining Unemployment In West Kalimantan period from 2010 to 2014". Withthe goal of Test and analyze the effect of economic growth and investment inexplaining unemployment districts / cities in West Kalimantan.The method used in this type of research is explanatory research by usingsecondary data, panel data comprising data time series and cross section from 2010to 2014. The program processed by computer using software economics views (Eviews).using fixed effect method Panel Least Square (PLS).The results of the discussion concluded that based on the t-statistic ofeconomic growth has a significant impact on unemployment with a probabilityvalue of 0.0002 is less than 0.05%, and the investment has no significant effect onunemployment with a probability value greater than 0.2447 0.05%. While the f-teststatistic (synchronously) can be seen from the probability value of 0.0000020 fstatisticis less than 0.05%, which means together economic growth and theinvestment effect on unemployment. Determination test showed R2 value of0.797644 79,76% variable means that unemployment can be explained by economicgrowth and investment.Keywords: Unemployment, economic growth and investment